2022
DOI: 10.3390/plants11131709
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light Intensity on the Growth and Antioxidant Activity of Sweet Basil and Lettuce

Abstract: Light and nutrients are among the most important factors for sustained plant production in agriculture. As one of the goals of the European Green Deal strategy is to reduce energy consumption, greenhouse growers focus on high-value crop cultivation with less-energy-demanding growing systems. This study aimed to evaluate the effect of fertilization at different light intensities on the growth of lettuce and basil and the activity of the antioxidant system. Sweet basil (Ocimum basilicum, ‘Opal’) and lettuce (Lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 44 publications
2
5
1
Order By: Relevance
“…We also showed that CGA accumulates in photosynthetically active organs like stems and leaves and its accumulation is higher when leaves are exposed to high light indicating that CGA biosynthesis is regulated by light intensity. This is consistent with the evidence that under high light conditions, the total amount of phenolics increases and is accompanied by induction of several genes of the phenylpropanoid pathway (Linatoc et al, 2018;Peŕez-Loṕez et al, 2018;Sutulienėet al, 2022). Photosynthesis is a vital process for the plant which requires protection from harmful UV light and from toxic molecules, like ROS, usually produced by plant cells during normal photosynthesis.…”
Section: Role Of Cgas In Photosynthetically and Non-photosyntheticall...supporting
confidence: 89%
“…We also showed that CGA accumulates in photosynthetically active organs like stems and leaves and its accumulation is higher when leaves are exposed to high light indicating that CGA biosynthesis is regulated by light intensity. This is consistent with the evidence that under high light conditions, the total amount of phenolics increases and is accompanied by induction of several genes of the phenylpropanoid pathway (Linatoc et al, 2018;Peŕez-Loṕez et al, 2018;Sutulienėet al, 2022). Photosynthesis is a vital process for the plant which requires protection from harmful UV light and from toxic molecules, like ROS, usually produced by plant cells during normal photosynthesis.…”
Section: Role Of Cgas In Photosynthetically and Non-photosyntheticall...supporting
confidence: 89%
“…We confirmed that TFC was significantly increased in both the flavonoid pathway-related DEGs. Furthermore, light intensity affects antioxidant system activity in basil and lettuce; for example, under strong light intensity, the DPPH, ABTS, and FRAP showed decreased activities in basil, and increased activity in lettuce (Sutulienėet al, 2022). Although the effects of light intensity on antioxidant activity have been reported in other plants, we did not observe significant differences in fennel under different light conditions, unlike in the case of CO 2 .…”
Section: B a Figurecontrasting
confidence: 69%
“…Assimilate used for high respiration causes assimilate to be transported to lower plant parts, resulting in low plant growth. Low light intensity caused a decrease in the rate of photosynthesis and carbohydrate synthesis, thereby limiting plant growth [13].…”
Section: Discussionmentioning
confidence: 99%